The New Normal? Work, Family, and Higher Education under COVID-19 - Mannon, Susan E. (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
Accounts of the social and economic changes brought on by COVID-19 describe these changes as the “new normal.” I argue that these changes are actually an extension of existing trends. For five decades, neoliberal reforms have resulted in the privatization and corporatization of everyday life, reshaping social institutions in the process. Of these institutions, the contemporary university is particularly important because it is both a workplace and a training ground in which neoliberal norms around competition, achievement, and individualism are enforced and promoted. This situation has socialized a new class of professionals to be productive workers who expect very little from their government, which is particularly problematic for women attempting to balance work and family life. To explore what this means under pandemic conditions, I draw on the life of Angelica, a woman who traded a life of drug addiction and welfare dependency for college attainment and professional work. College should have liberated her; instead, it has left her with a demanding job and little to no institutional help. I compare what is expected of Angelica as a college-educated working mother under the pandemic and what was expected of me as a professor and mother before the pandemic, suggesting important continuities in the pace of work, the nature of care, and the expectations of the self and others.